2006
DOI: 10.4067/s0034-98872006001100007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de una unidad de tratamiento del ataque cerebral en un hospital universitario

Abstract: US$ 5.550 and US$ 4.815, respectively (p =ns). Conclusions: The Stroke Unit decreases hospital stay days without raising costs importantly. The inclusion criteria for stroke patients admitted to the Unit were adequate and the stroke registry allowed a good assessment of the Unit operation (Rev Méd Chile 2006; 134: 1402-08).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
2
0
2
Order By: Relevance
“…There is little data on the pattern of stroke sub‐types in South America and poor characterization of specific risk factors in the region . Although data from some hospital‐based stroke registries have shown that the rate of patients with cerebral hemorrhages is from two to three times higher than that reported in the developed world, other studies suggest that the pattern of stroke sub‐types is similar to that seen in North America and Europe . Proposed arguments to explain the variability among South American stroke registries include: differences in race‐ethnicity, lifestyle, environmental conditions, or even a selection bias of some studies, i.e., patients with less severe (ischemic) strokes not attending hospitals in less developed areas.…”
Section: Comparison Of Demographic Profile Risk Factors and Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little data on the pattern of stroke sub‐types in South America and poor characterization of specific risk factors in the region . Although data from some hospital‐based stroke registries have shown that the rate of patients with cerebral hemorrhages is from two to three times higher than that reported in the developed world, other studies suggest that the pattern of stroke sub‐types is similar to that seen in North America and Europe . Proposed arguments to explain the variability among South American stroke registries include: differences in race‐ethnicity, lifestyle, environmental conditions, or even a selection bias of some studies, i.e., patients with less severe (ischemic) strokes not attending hospitals in less developed areas.…”
Section: Comparison Of Demographic Profile Risk Factors and Patternmentioning
confidence: 99%
“…High rates of cerebral hemorrhages (approaching 40% of stroke cases) reported in some pioneer registries during the 1990s (2,4) have not been duplicated in more recent studies. In contrast, almost all studies recruiting patients from 2003 on reported less than 20% of cerebral hemorrhages among their strokes cases (9)(10)(11)(12)(13). Intermediate rates of hemorrhagic strokes (from 25% to 27%) were noted among registries recruiting patients by the end of the 20th century and the start of the new millennium (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…literatura describe una larga data en la existencia de estas unidades, evidenciando positivos indicadores de pronóstico y mortalidad, gracias al manejo médico, repercutiendo favorablemente en el déficit cerebral (16) . Álvarez-Sabín (17) demostraron la eficacia en la reducción de estancia hospitalaria, mortalidad e institucionalización, posterior a la implementación de una atención protocolizada y especializada en 5.843 usuarios con ACV.…”
Section: Sección B: Antecedentes Clínicosunclassified
“…Ello implica que aquí se establece un vínculo con la presencia de factores de riesgo cardiovascular de manera individual, fundamentalmente la resistencia a la insulina, más que a la presencia del SOPQ y la hiperandrogenemia. 7 Una experiencia de un equipo chileno 8 , meritoria de profundización, muestra cómo las denominadas Unidades de Tratamiento del Ataque Cerebral (UTAC) del Hospital Clínico de la Universidad de Chile (HCUCH), especializadas y diseñadas concretamente para el tratamiento de la ECV aguda, pueden reducir la penumbra isquémica. Esto apunta a que de esta manera es posible optimizar la neuroprotección, sorteando las complicaciones o interviniéndolas tempranamente y alcanzando con celeridad el diagnóstico etiológico.…”
Section: Desarrollounclassified